Comparison between sevoflurane and propofol on immunomodulation in an in vitro model of sepsis - Oliveira, Tainá B.; Braga, Cassia L.; Battaglini, Denise; Pelosi, Paolo; Rocco, Patricia R. M.; Silva, Pedro L.; Cruz, Fernanda F. (Frontiers in Medicine, 2023)
Patients with sepsis often require sedation and/or anesthesia. Although the immunomodulatory effects of anesthetics have been increasingly recognized, the molecular mechanisms require better elucidation. We compared the effects of sevoflurane with propofol on the expression of pro-and anti-inflammatory biomarkers released by monocytes/macrophages and blood/bronchoalveolar lavage fluid (BALF) neutrophils, the phagocytic capacity of monocytes/macrophages, and neutrophil migration, as well as mediators associated with alveolar epithelial and endothelial cells obtained from rats with sepsis. Polymicrobial sepsis was induced by cecal ligation and puncture in nine male Wistar rats. After 48 h, animals were euthanized and their monocytes/alveolar macrophages, blood and BALF neutrophils, as well as alveolar epithelial and endothelial cells were extracted, and then exposed to (1) sevoflurane (1 minimal alveolar concentration), ( 2) propofol (50 µM), or (3) saline, control (CTRL) for 1 h. Sevoflurane reduced interleukin (IL)-6 mRNA expression in monocytes and alveolar macrophages (P=0.007, P=0.029), whereas propofol decreased IL-6 mRNA only in alveolar macrophages (P=0.027) compared with CTRL. Sevoflurane increased IL-10 expression (P=0.0002) in monocytes compared with propofol and increased IL-10 mRNA and transforming growth factor (TGF)-β mRNA (P=0.037, P=0.045) compared with CTRL. Both sevoflurane and propofol did not affect mRNA expression of IL-10 and TGF-β in alveolar macrophages. The phagocytic capacity of monocytes (P=0.0006) and alveolar macrophages (P=0.0004) was higher with sevoflurane compared with propofol. Sevoflurane, compared with CTRL, reduced IL-1β mRNA (P=0.003, P=0.009) and C-X-C chemokine receptor 2 mRNA (CXCR2, P=0.032 and P=0.042) in blood and BALF neutrophils, and increased CXCR4 mRNA only in BALF neutrophils (P=0.004). Sevoflurane increased blood neutrophil migration (P=0.015) compared with propofol. Both sevoflurane and propofol increased zonula occludens-1 mRNA (P=0.046, P=0.003) in alveolar epithelial cells and reduced Toll-like receptor 4 mRNA (P=0.043, P=0.006) in alveolar endothelial cells compared with CTRL. Only propofol reduced surfactant protein B mRNA (P=0.028) in alveolar epithelial cells. Sevoflurane, compared with propofol, increased anti-inflammatory biomarkers in monocytes, but not in alveolar macrophages, enhanced monocyte/alveolar macrophage phagocytic capacity and increased neutrophil migration in in vitro experimental sepsis. Both propofol and sevoflurane protected lung epithelial and endothelial cells.